2017
DOI: 10.1080/15368378.2017.1389752
|View full text |Cite
|
Sign up to set email alerts
|

Bio-soliton model that predicts non-thermal electromagnetic frequency bands, that either stabilize or destabilize living cells

Abstract: Solitons, as self-reinforcing solitary waves, interact with complex biological phenomena such as cellular self-organization. A soliton model is able to describe a spectrum of electromagnetism modalities that can be applied to understand the physical principles of biological effects in living cells, as caused by endogenous and exogenous electromagnetic fields and is compatible with quantum coherence. A bio-soliton model is proposed, that enables to predict which eigen-frequencies of non-thermal electromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 94 publications
3
31
0
Order By: Relevance
“…The theoretical background of the found regularities of patterns is that nature evidently organizes its components at a highly coherent semi-harmonic like way combined with energy minimization [1] [3]. But also non-coherent patterns were revealed, that show life-decaying electromagnetic frequency effects.…”
Section: The Quantum-biological Basis For Coherent Andmentioning
confidence: 98%
See 2 more Smart Citations
“…The theoretical background of the found regularities of patterns is that nature evidently organizes its components at a highly coherent semi-harmonic like way combined with energy minimization [1] [3]. But also non-coherent patterns were revealed, that show life-decaying electromagnetic frequency effects.…”
Section: The Quantum-biological Basis For Coherent Andmentioning
confidence: 98%
“…Solitons are self-reinforcing solitary waves that interact with complex biological phenomena such as cellular self-organization. The soliton model is able to describe a spectrum of electromagnetism modalities that can be applied to understand the physical principles of biological effects in living cells, as caused by endogenous and exogenous electromagnetic fields and is compatible with quantum coherence [1]. It has been found that that the first, second, and third harmonics of waves can be united within a broad range of frequencies from sub Hertz till about 10 25 Hz by dividing 2:3 ratios and approximations thereof over 1:2 ratios [3].…”
Section: The Quantum-biological Basis For Coherent Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of quantum theories posit the existence of a quasiparticle known as the phonon, a quantum field-equivalent for sonic, or vibrational, atomic interactions first conceived of by the Soviet physicist Igor Tamm (Feinberg & Igor'Evgen'evich Tamm, 1995). Theoretical has since proven to be reality, as the phonon is now widely accepted as a quantum mechanical solution to superfluid and condensate equations, and is postulated to be involved with various biological processes (Geesink & Meijer, 2016;Kogar et al, 2017;Scalapino, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By improving his model, Pan Xiao-feng presented that the Davydov soliton is the basic transformed unit of energy and information in bio-system included human body [4] [5]. Many facts also reveal that the bio-solitons sometimes can be seen as electrically longitudinal vibrations travelling along proteins, microtubules and DNA, etc., including interfering with local resonant oscillations by excitation of neighboring molecules and macromolecules [6], for example, C. W. Smith presented a model of ideal cell resonance [7] and Fröhlich presented the coherent oscillation of bio-system in 1978 [8] [9], etc. However, is it possible that this kind of oscillation as a macro-quantum condensation can take place in our body?…”
Section: Introductionmentioning
confidence: 99%